Doping Control of Magnetic Anisotropy for Stable Antiskyrmion Formation in Schreibersite (Fe, Ni)3P with S4 symmetry. Issue 11 (5th February 2022) - Karube, Kosuke; Peng, Licong; Masell, Jan; Hemmida, Mamoun; Krug von Nidda, Hans‐Albrecht; Kézsmárki, István; Yu, Xiuzhen; Tokura, Yoshinori; Taguchi, Yasujiro
Abstract: Magnetic skyrmions, vortex‐like topological spin textures, have attracted much interest in a wide range of research fields from fundamental physics to spintronics applications. Recently, growing attention is also paid to antiskyrmions emerging with opposite topological charge in non‐centrosymmetric magnets with D 2d or S 4 symmetry. In these magnets, complex interplay among anisotropic Dzyaloshinskii–Moriya interaction, uniaxial magnetic anisotropy, and magnetic dipolar interactions generates various magnetic textures. However, the precise role of these magnetic interactions in stabilizing antiskyrmions remains to be elucidated. In this work, the uniaxial magnetic anisotropy of schreibersite (Fe, Ni)3 P with S 4 symmetry is controlled by doping and its impact on the stability of antiskyrmions is investigated. The authors' magnetometry study, supported by ferromagnetic resonance spectroscopy, shows that the variation of the Ni content and slight doping with 4d transition metals considerably change the magnetic anisotropy. In particular, doping with Pd induces easy‐axis anisotropy, giving rise to formation of antiskyrmions, while a temperature‐induced spin reorientation is observed in an Rh‐doped compound. In combination with Lorentz transmission electron microscopy and micromagnetic simulations, the stability of antiskyrmion as functions of uniaxial anisotropy and demagnetization energy is quantitatively analyzed, and demonstrated that subtle balance between them is necessary to stabilize the antiskyrmions. Abstract : The magnetic anisotropy of schreibersite (Fe, Ni)3 P with S 4 symmetry is controlled by doping and its impact on the stability of antiskyrmions is investigated. It is demonstrated that the variation of the Ni content and slight doping with 4d transition metals considerably change the magnetic anisotropy, and subtle balance between uniaxial anisotropy and demagnetization energy is necessary to stabilize the antiskyrmions.